Characteristics of Adults Managing Vitamins/Supplements and Prescribed Medications–Who Is Using, Not Using, and Abandoning Use of Pillboxes?: A Descriptive Study. Issue 5 (September 2018) - Bartlett Ellis, Rebecca J.; Ganci, Aaron; Head, Katharine J.; Ofner, Susan
Abstract : Purpose: Evidence suggests pillboxes are effective for improving medication adherence. However, prior descriptive studies about pillbox use are limited to studies of older adults or condition-specific studies. This study describes characteristics of adults with chronic conditions and their use of pillboxes. Methods: A survey questionnaire link was posted on a social media recruitment page from August 2016 to April 2017. Results: The sample of 179 people was middle-age (47.7 ± 15.4 years), predominantly white (90.4%), educated (>93% educated beyond high school), female (n = 148; men n = 26), married/partner (58.2%), and working full time (55.9%). Pillboxes were used by 66% (n = 118) of the sample at some point; 22.9% reported pillbox abandonment. Compared with people who never used a pillbox, current pillbox users were older (53.2 ± 14.3 vs 42.0 ± 14.4 years; P < .001) and took more vitamins/supplements (3.9 ± 3.8 vs 2 ± 1.8, P = .002) and prescribed medications (4.2 ± 2.2 vs 2.6 ± 1.9, P < .001). Adherence did not differ between groups; pillbox users were more likely to refill medications before running out compared with those abandoning use, P < .001. Conclusion: Age and number of medications may affect pillbox use. Future research should explore barriers to continued use of pillboxes and uptake in younger populations.